English – Vietnamese translation of Odontology terms in Odontology materials used for Vietnamese dentists = Nghiên cứu dịch thuật Anh – Việt các thuật ngữ Nha khoa trong các tài liệu Nha khoa sử dụng cho Nha sĩ Việt Nam - Nguyễn, Thu Hằng (2020)
This thesis aimed to investigate the translation strategiesprocedures of the dental terms in the dictionary “Thuật ngữ Răng Hàm Mặt” by the Faculty of Odonto-Stomatology, Ho Chi Minh Pharmaceutical – Medical University, 1993; and the book “Dental Terminology” by Charline M. Dofka, published by Delmar, Cengage Learning, 2012, combined with the field notes taken by the researcher. The notes included the commonly-used translation strategiesprocedures for the translator – the researcher - between doctors and patients or clients, who are the participants in this study in a dental clinic. The thesis uses the theoretical framework of translation procedures of Peter Newmark (1995) to classify the translation procedures of those terms and compare with the actual practice of translation. The findings of the research reveal that, in some circumstances, many Vietnamese dental terms do not make easy sense to the doctors and patients or clients because they are mostly academic or professional terms. The paraphrased terms the book “Dental terminology” and their synonyms are helpful in making them more easily-understood. The paraphrasing and synonymy procedures by Peter Newmark are also the most usefuleffective strategies ones apart from the others which are: literal translation, transference, naturalization, descriptive equivalence, cultural equivalence, shift or transposition and omission. The study suggests practical applications of translation strategiesprocedures in real-life dental translating contexts in Vietnam.